The Influence of Seniors in Improving the Arabic Speaking Skills of New College Student - Ahmad Nurul Huda Salmas; Uril Bahruddin; Syuhadak Syuhadak; Gareeb Allah Babiker Mustafa Babiker (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research explained the role of seniors in assisting new students at Sekolah Tinggi Ilmu Bahasa Arab (STIBA) in enhancing their Arabic speaking proficiency. The research methodology employed in this study is qualitative research and case study design. Data are gathered through observations and interviews. The findings of this research indicate that seniors have a significant impact on helping new students to improve their Arabic speaking skills at STIBA Ar-Rayyah. Seniors serve as mentors, peers, and a support system that provides positive encouragement to new students. They offer guidance and support both within the campus dormitories and outside, engaging in various activities where Arabic is the primary communication language. Seniors also motivate and help new students gain confidence in speaking Arabic and overcome learning obstacles. This research underscores the importance of non-academic aspects in the educational institution, such as motivation and emotional support, which can have a positive impact on academic performance and personal development of students. The role of seniors at STIBA Ar-Rayyah fosters a conducive learning environment that aids new students in enhancing their Arabic speaking skills